Mot ett gemensamt perspektiv : En studie bland de huvudsakliga aktörerna i Luleå - Johansson, Emma; Stenberg, Rebecca (2016)
The branding of destinations is becoming increasingly important in today’s marketing climate. The reasons for this are many, but most significantly for cities, towns and regions to increase visitors, residents and attract businesses. But the process of branding a destination is more complex than branding a product. In destination marketing, there are several parties’ involved, called stakeholders. To successfully brand a destination, cooperation between stakeholders that can align their interests in the process is favorable. To be able to go through a branding process one must be aware of what the brand ought to include; the current perceptions and the desired perceptions of a destination. Luleå has been used as the sample for this study, which aims to find the major stakeholders interested in forming a strong brand around Luleå, and their perceptions of the city. This is to lay the foundation as to a possible future branding process. The four stakeholder groups included in this case study are residents of Luleå, visitors, hotel businesses and the municipality. Two major areas of concern were discovered alongside a few others, shared by these stakeholders. The first major one, which aligned the stakeholder’s opinions, was the natural resource of beautiful nature that Luleå has to offer. The second one was the current housing crisis that causes problems on many levels for all the stakeholders. Luleå needs to build on the fact that they have access to nature and make it part of their brand as their greatest strength and find a satisfactory way of dealing with the housing crisis. The municipality stated that Luleå is a “sustainable coastal city in constant evolution” and the other stakeholders stated their appreciation for nature and the possibilities that Luleå has to offer. Validerat; 20160627 (global_studentproject_submitter)